TAKSONOMI BLOOM DAN IMPLEMENTASI KURIKULUM BERBASIS MULTIKULTURAL - Moh Irmawan Jauhari (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2017)
Bloom taxonomy is oriented to make learning pierced three areas. Those are cognitive, affective, and psychomotor. Given that the purpose of holding the education is not only cognitive matters. This is (then) what makes learning which held in educational institution becomes more valuable at forming learner’s character. Multicultural-based curriculum is considered necessary to apply in education. Given that the world of education is inseparable from real life experienced by learner’s every day. If education is increasingly affirming multicultural reality as well as trying to make it a big capital for change, then it needs further formulation, discussion and established about multicultural curriculum. But certainly, the multicultural-based curriculum exists in Indonesia actually trying to emphasize that multicultural education in Indonesia is more complex both vertical and horizontal. And there are small, yet simple, sentiments that are needed to be scraped in the educational space, for the better future of the Indonesian nations while maintaining the multicultural conditions.Key words: Taxonomy, Curriculum, Multicultural